The onco-psychiatry in breast cancer: considerations about the female matter (Archives of Clinical Psychiatry, 2006)
The authors performed a broad literature review about psychiatric factors in breast cancer. Inside the master reasoning of the surgical and oncological treatments, an emphasis was made on heir impact over the mental health. Aspects like surgical possibilities and body image and its impact over the self-estime and sexuality and systemic treatments and their physical consequences, like fatigue, nausea and vomiting were discussed. The differences between the aged groups treated also were considered, separating their issues. Topics about Quality of Life was always considered. Questions about pharmacological and psychotherapeutical approach were considered too, including alternative medicine.